Design and Implement a Real Network in EPANET Tool and Detect Leak through Head Loss - Neeraj, Meenakshi Nawal, Mahesh Bundele, P. K. Suri (International Journal of Modern Agriculture, 2021)
Water distribution network (WDN) to design using EPANET tool for my problem statement areaGurthali, NARWANA-JIND, HARYANA and objective of this paper to improve in my previous simulation work. In this paper introduce the EPANET tool with installation and required tool for this. In EPANET tool we can also detect the leakage with a new method that is called Hazen-Williams and Chezy-Manning. In my previous paper I have discussed Darcy Weisbach method in detail my previous research paper.